2022
DOI: 10.3390/ijms23031449
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Small Extracellular Vesicles in the Cerebral Metastatic Process

Abstract: Brain metastases represent more than 50% of all cerebral tumors encountered in clinical practice. Recently, there has been increased interest in the study of extracellular vesicles, and the knowledge about exosomes is constantly expanding. Exosomes are drivers for organotropic metastatic spread, playing important roles in the brain metastatic process by increasing the permeability of the blood–brain barrier and preparing the premetastatic niche. The promising results of the latest experimental studies raise th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Thus, an improved molecular understanding of the metastatic process with the aim of discovering new adjuvant treatments is necessary. It has previously been shown that brain metastasis development is mediated by complex interactions between tumour cells and normal cells, facilitated in part by the transfer of EVs to establish a metastasis‐promoting environment (Gowda et al., 2020 ; Tamas et al., 2022 ). To our knowledge this is the first study showing that MBM‐EVs pretreatment increases brain metastasis burden in mice (Figure 1e,f ), possibly due to increased transmigration of tumour cells through the BBB or improved survival of those cells already transmigrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an improved molecular understanding of the metastatic process with the aim of discovering new adjuvant treatments is necessary. It has previously been shown that brain metastasis development is mediated by complex interactions between tumour cells and normal cells, facilitated in part by the transfer of EVs to establish a metastasis‐promoting environment (Gowda et al., 2020 ; Tamas et al., 2022 ). To our knowledge this is the first study showing that MBM‐EVs pretreatment increases brain metastasis burden in mice (Figure 1e,f ), possibly due to increased transmigration of tumour cells through the BBB or improved survival of those cells already transmigrated.…”
Section: Discussionmentioning
confidence: 99%
“…A major contributing factor to niche remodelling is the transfer of small extracellular vesicles (EVs) of endocytic origin from tumour cells (Peinado et al., 2017 ; Tamas et al., 2022 ). The EVs shuttle proteins, DNA, and RNA, mostly in the form of miRNAs, to both local and distant cells (Cesi et al., 2016 ; Valadi et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Functional assays linked the presence of TIMs and TAMs with the exhaustion of cytotoxic and The mechanisms through which specific organs are targeted by primary tumors and how they form niches remain under investigation. Some of the most promising candidates are tumor-derived exosomes, which carry surface proteins with organotropic signatures [38,39]. This allows organotropism in a range of different cancer types via variations in integrin expression in endothelial cells [40].…”
Section: General Concepts Of the Pre-metastatic Nichementioning
confidence: 99%
“…EV-mediated intracellular communication plays a role not only in maintaining cell homeostasis, but also in disease progression [ 96 , 97 , 98 , 99 ]. Exosomes are associated with several diseases, including cancer metastasis, which is the invasion and spread of primary cancer cells into other organs [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ]. Exosomes have been shown to play an important role in the formation of the cancer microenvironment and the mechanisms of cancer malignancy, such as cancer cell growth, infiltration, metastasis, and pre-metastasis niche [ 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ].…”
Section: Evs In Cancer Metastasis and Malignant Transformationmentioning
confidence: 99%